2021
DOI: 10.3390/membranes11080616
|View full text |Cite
|
Sign up to set email alerts
|

Economics and Energy Consumption of Brackish Water Reverse Osmosis Desalination: Innovations and Impacts of Feedwater Quality

Abstract: Brackish water desalination, using the reverse osmosis (BWRO) process, has become common in global regions, where vast reserves of brackish groundwater are found (e.g., the United States, North Africa). A literature survey and detailed analyses of several BWRO facilities in Florida have revealed some interesting and valuable information on the costs and energy use. Depending on the capacity, water quality, and additional scope items, the capital cost (CAPEX) ranges from USD 500 to USD 2947/m3 of the capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The published range for the unit cost for brackish water RO desalination for 10,000 to 70,000 m 3 /d capacities and 2000–6000 mg/L are 0.39–0.66 USD/m 3 [ 15 , 16 ]. It is worth mentioning that using electrodialysis for brackish water desalination may be lower by 5–33% according to the capacity (Generous et al, 2021).…”
Section: Financial Indicators For Zld Systemmentioning
confidence: 99%
“…The published range for the unit cost for brackish water RO desalination for 10,000 to 70,000 m 3 /d capacities and 2000–6000 mg/L are 0.39–0.66 USD/m 3 [ 15 , 16 ]. It is worth mentioning that using electrodialysis for brackish water desalination may be lower by 5–33% according to the capacity (Generous et al, 2021).…”
Section: Financial Indicators For Zld Systemmentioning
confidence: 99%
“…Conventional technologies of water treatment (such as sedimentation, adsorption and filtration) simply transfer the contaminants from one medium to another one, without destroying the pollutants. Unfortunately, some of these methodologies (such as reverse osmosis) have high operating and energetic costs [ 61 ]. Heterogeneous photocatalysis is one of the emergent and innovative methods for wastewater treatment.…”
Section: Polymethacrylate: Applicationsmentioning
confidence: 99%
“…The tap water was produced through seawater reverse osmosis (SWRO) desalination at the King Abdullah University of Science and Technology desalination plant (Thuwal, Jeddah, Saudi Arabia). Previous studies have shown that the tap water used for this experiment is suitable for biofilm studies [10,[34][35][36]. The tap water elemental composition can be found in Table S1 of the Supplementary Material.…”
Section: Experimental Setup and Operational Parameters During Biofilm...mentioning
confidence: 99%